UIN Bandung Community Service: Fun Learning Boosts Student Motivation at SDN Mekarbakti, Mekarsari Village - Al Mighwar, Muhammad; Kusnawan, Aep; Supratman, Iman; Husen Sobana, Dadang; Suci Asih, Vemy; Sopiah, Evi; Siti Nurazizah, Fitri; Saepul Akbar, Yosep; Rifaldy, Rizky (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
The Community Engagement Program (KKN) of UIN Bandung in 2023 was organized and implemented based on Community Empowerment (Sisdamas), with a focus on fostering Religious Moderation in villages, tailored to community needs and the academic backgrounds of participating students. Through the Fun Learning method, the initiative aimed to boost student learning motivation at SDN Mekarbakti, Mekarsari Village, Bandung Regency. By integrating Participatory Action Research and qualitative research approaches, the implementation of Fun Learning methods, including educational games, arts and creativity activities, group discussions, and class projects, proceeded through four structured cycles: citizen meetings and social reflection, community organizing and social mapping, participation planning, action, monitoring, and evaluation. The results of community empowerment demonstrated a significant boost in student participation, interest in learning, academic performance, and positive feedback from teachers and parents. They assessed that this learning approach was more effective in enhancing student motivation than conventional methods, aligning with various contemporary theories and research findings.